Lymphoma in a Young Patient with Demoralization Syndrome: Case Report - Utria Castro, Jhoan; Gaviria , Luisa María; López Castellanos, Nicolás; Muñoz Ortega , Paola Andrea (Arandu UTIC, 2025)
Introduction: This case illustrates a demoralization syndrome in the setting of palliative care for advanced lymphoma and emphasizes the necessity of a biopsychosocial approach to care. Demoralization is a syndrome of hopelessness, meaninglessness and existential distress that is commonly underrecognized in young adult patients at the end of life. Main Findings: A 21-year-old patient with Hodgkin lymphoma in previous remission presented with tumor reactivation, severe abdominal pain, and profound emotional deterioration. Symptoms included emotional withdrawal, disrupted sleep, and loss of meaning, which were indicative of demoralization. Interventions and Outcomes: Multidisciplinary palliative therapy consisted of advanced analgesia therapy with hydromorphone and infusion of lidocaine, parenteral nutrition, and cognitive behavioral psychological care. Notwithstanding these interventions, the patient experienced an emotional deterioration with no therapeutic comeback possible. Conclusion: This case emphasizes the importance of comprehensive and age-appropriate interventions to identify and manage demoralization early in the course of terminal illnesses, improving quality of life and preserving patient dignity in end-of-life care.